The Effect of China’s Universal Two-Child Policy on Female Employment: A Mixed-Methods Analysis of Labor Market Outcomes - Zhao, Sijia (AUC Knowledge Fountain, 2025)
This study analyzes the effects of China's Universal Two-Child Policy, enacted in 2016, on women's employment outcomes. The implementation of this policy has highlighted the challenges women face in the labor market, revealing a significant disparity between the policy's effects and expectations, as evidenced by the simultaneous occurrence of low fertility intentions and employment difficulties. This research employs a mixed methodology to systematically evaluate the policy's effects on the quality and stability of women's employment while also investigating the underlying mechanisms of this impact. The research indicates that the Universal Two-Child Policy adversely affects women's employment performance in multiple dimensions. Quantitative analyses indicated that second births significantly decreased women's income levels. Qualitative interviews further demonstrated that women's work engagement and efficiency typically declined despite no substantial change in the working hours. Regarding employment satisfaction, only a few women in particular roles and sectors reported increased happiness associated with larger family sizes, whereas most respondents exhibited negative sentiments. Quantitative findings indicate that childbearing behavior diminishes labor force participation, while qualitative research corroborates the occurrence of career interruptions that influence women's career trajectories. An analysis of the underlying causes reveals that the impact mechanism entails a complex interaction among family responsibilities, economic development, and labor market structure. Rising costs linked to alterations in family structure, the efficiency focus of businesses, gender-biased employment practices, conventional cultural norms, and insufficient policy support systems collectively create obstacles to achieving work-family balance for women. This thesis recommends enhancing anti-employment discrimination mechanisms, bolstering the government's regulatory role, refining the public service system, and implementing a gender impact assessment mechanism to facilitate the integrated advancement of fertility policy and employment security.